Changes in cardiac and vascular haemodynamics as potential mediators of improvements in cardiovascular and kidney outcomes with empagliflozin in type 2 diabetes - Krämer, Bernhard; Hauske, Sibylle J.; Chilton, Robert; Mann, Johannes F. E.; Gullestad, Lars; Fitchett, David; Mattheus, Michaela; Steubl, Dominik; Wanner, Christoph (Journal of diabetes and its complications, 2023)
Aims - Evaluate changes in haemodynamic markers as mediators of cardiovascular (CV) and kidney benefits with empagliflozin. - Methods - Post-hoc analysis of EMPA-REG OUTCOME in patients with type 2 diabetes (T2D) and established CV disease receiving empagliflozin (10 and 25 mg) or placebo. Outcomes were CV death, hospitalisation for heart failure [HF], HF death, incident/worsening nephropathy, new onset macroalbuminuria, and the composite of sustained estimated glomerular filtration rate decline ≥40 % from baseline, renal replacement therapy or renal death. To be considered a mediator, changes in variable (pulse pressure, mean arterial pressure and cardiac workload) over time had to be (1) affected by active treatment, (2) associated with the outcome, and (3) adjustment for changes over time must reduce treatment effect versus an unadjusted analysis. Variables were evaluated in Cox regression analyses. - Results - Pulse pressure, mean arterial pressure and cardiac workload were significantly reduced by empagliflozin vs placebo. Using change from baseline to Week 12 or sensitivity analyses (time-dependent updated mean and current change from baseline) of these CV parameters, only small impacts on empagliflozin effect on CV and kidney outcomes were shown. - Conclusions - Improvements in haemodynamic parameters did not substantially mediate empagliflozin benefits on CV and kidney outcomes in patients with T2DM and established CV disease.
Online verfügbar: 17. August 2023, Artikelversion: 24. August 2023
Gesehen am 18.09.2024